A diagnostic evaluation of real‐time PCR, fluorescent antibody and microscopic agglutination tests in cases of equine leptospiral abortion. (23rd May 2014) - Erol, E.; Jackson, C. B.; Steinman, M.; Meares, K.; Donahoe, J.; Kelly, N.; Locke, S.; Smith, J. L.; Carter, C. N.
Summary Reasons for performing study A comprehensive evaluation of the real‐time PCR assay for leptospirosis in comparison with other diagnostic assays on a large‐scale basis is fundamental in validating the assay and determining the causes of equine abortions. Objectives To compare and evaluate the diagnostic value of real‐time PCR assay for leptospirosis with traditional methods in equine leptospiral abortions. Study design Cross‐sectional observational study. Methods A Leptospira spp. fluorescent antibody test (FAT), microscopic agglutination test (MAT) and real‐time PCR (targeting the LipL32 gene) were compared and evaluated in equine fetal necropsy specimens (placenta, kidney, liver and heart blood) and maternal serum (when available) in 339 equine fetuses. Results From a total of 339 equine fetuses necropsied, 21 cases (6.19%) were diagnosed as leptospiral abortion. The majority of leptospiral abortions occurred in January (8 cases) and February (5 cases). Real‐time PCR detected 21 of 21 cases, whereas MAT and FAT detected 19 and 18 (including 2 suspicious cases) cases, respectively. Comparing tissues, placenta yielded somewhat similar cycle of threshold values by real‐time PCR compared with kidney, whereas kidney was the best specimen for the diagnosis of leptospirosis by the FAT test. In all MAT positive cases, the predominant titre in fetal heart blood was to serovar Pomona (ranging 1:100 to 1:204, 800) with little or no cross‐reaction to serovar Grippotyphosa. Conclusions The results indicate that real‐time PCR is an effective method for the diagnosis of leptospiral abortion in horses. However, MAT should continue to be used in clinical cases for serovar determination.